Pengaruh Capital Adequacy Ratio, Non Performing Loan, Ukuran Perusahaan dan Struktur Kepemilikan Terhadap Profitabilitas Bank yang Terdaftar di BEI di Periode 2008-2011 - Kencana, Pranabawa Adi (E-Jurnal Akuntansi, 2012)
Effect of Capital Adequacy Ratio, Non Performing Loan, Firm Size and Ownership Structure to profitability of banks listed on the BEI in the period 2008-2011. This research is performed in order to test the influence of the Capital Adequacy Ratio, Non Performing Loan, firm size and ownership structure to profitability of banks listed on the Indonesia Stock Exchange in the period 2008-2011. The sampling method used is the method of probability sampling with simple random sampling technique . Analysis technique used is doubled regression with F-statistic and t-statistic. From the results obtained by simultaneous F test results that Capital Adequacy Ratio, Non Performing Loans, firm size and ownership structure significantly influence the profitability of the banks listed in the Indonesia Stock Exchange. Meanwhile, the results of the t test that Capital Adequacy Ratio, Non Performing Loans, firm size and ownership structure in partial significant to profitability of banks listed on the Indonesia Stock Exchange. Keyword : Capital Adequacy Ratio, Non Performing Loan, Firm Size, Ownership Structure, and Profitability.